EFFORTS TO PREVENT CRIME OF CORRUPTION THROUGH STUDENT PARTICIPATION IN THE CAMPUS ENVIRONMENT - Fika Fauzah; Ligar Larasati; Abdul Fahmi; Sanjaya, Rian (Fakultas Hukum Universitas Djuanda, 2023)
The problem of corruption in Indonesia, which is increasingly rampant, starting from the central government, regional governments, to the joints of student life in general, requires an effective eradication strategy. One that must be involved in preventing and eradicating corruption is students. Students must take an active role in preventing corruption. One thing students can do is carry out anti-corruption education to students in general. It is hoped that the process of prosecuting corruption cases carried out by the KPK coupled with the anti-corruption education movement is expected to optimize the process of eradicating corruption in Indonesia. Results: The role of students in preventing corruption is by conducting outreach about the importance of preventing corruption, holding seminars on preventing corruption by bringing in experts, holding discussions about corruption, speaking out to the government.